Remdesivir potently inhibits carboxylesterase‐2 through covalent modifications: signifying strong drug‐drug interactions. (6th January 2021) - Shen, Yue; Eades, William; Yan, Bingfang
Abstract: Remdesivir was recently approved to treat COVID‐19. While this antiviral agent delivers clinical benefits, several safety concerns in many cases have been raised. This study reports that remdesivir at nanomolar concentrations inhibits carboxylesterase‐2 (CES2) through covalent modifications. CES2 is a major drug‐metabolizing enzyme. The combination of high potency with irreversible inhibition concludes that cautions must be exercised when remdesivir is used along with drugs hydrolyzed by CES2.